Identification of histone acetyltransferase genes responsible for cannabinoid synthesis in hemp - Yufei Cheng; Kang Ning; Yongzhong Chen; Cong Hou; Haibin Yu; Huatao Yu; Shilin Chen; Xiaotong Guo; Linlin Dong (BMC, 2023)
Abstract Background Histone acetyltransferases (HATs) play an important role in plant growth and development, stress response, and regulation of secondary metabolite biosynthesis. Hemp (Cannabis sativa L.) is famous for its high industrial, nutritional, and medicinal value. It contains non-psychoactive cannabinoid cannabidiol (CBD) and cannabinol (CBG), which play important roles as anti-inflammatory and anti-anxiety. At present, the involvement of HATs in the regulation of cannabinoid CBD and CBG synthesis has not been clarified. Methods The members of HAT genes family in hemp were systematically analyzed by bioinformatics analysis. In addition, the expression level of HATs and the level of histone acetylation modification were analyzed based on transcriptome data and protein modification data. Real-time quantitative PCR was used to verify the changes in gene expression levels after inhibitor treatment. The changes of CBD and CBG contents after inhibitor treatment were verified by HPLC-MS analysis. Results Here, 11 HAT genes were identified in the hemp genome. Phylogenetic analysis showed that hemp HAT family genes can be divided into six groups. Cannabinoid synthesis genes exhibited spatiotemporal specificity, and histones were acetylated in different inflorescence developmental stages. The expression of cannabinoid synthesis genes was inhibited and the content of CBD and CBG declined by 10% to 55% in the samples treated by HAT inhibitor (PU139). Results indicated that CsHAT genes may regulate cannabinoid synthesis through altering histone acetylation. Conclusions Our study provides genetic information of HATs responsible for cannabinoid synthesis, and offers a new approach for increasing the content of cannabinoid in hemp.